2023
DOI: 10.1029/2022ms003415
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network‐Based Scale‐Adaptive Cloud‐Fraction Scheme for GCMs

Abstract: Clouds play important roles in the Earth climate system. They dominate the energy budget by reflecting shortwave radiation and trapping longwave radiation (Wild et al., 2019), participate in the hydrological cycle via precipitation, and alter mass and energy vertical profiles by cloud venting (G. Chen et al., 2012;Yin et al., 2005) and latent-heat release. On the other hand, clouds are strongly coupled with aerosols and meteorology (Stevens & Feingold, 2009), involving complex feedbacks that span several tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Recognizing the importance of cloud dynamics for SIP, training RaFSIP using outputs from higher‐resolution km‐scale grids or even Large Eddy Simulation models would be imperative. In the context of growing convective clouds, where the HM process may surpass BR in efficiency (Waman et al., 2022), and DS may be more active due to the presence of larger raindrops, potential adaptations for a scale‐adaptive RaFSIP scheme (Chen et al., 2023) could be more urgent than in stratiform clouds. This is because of the scale dependence of LWC, which can be an important input for predicting the effect of HM.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the importance of cloud dynamics for SIP, training RaFSIP using outputs from higher‐resolution km‐scale grids or even Large Eddy Simulation models would be imperative. In the context of growing convective clouds, where the HM process may surpass BR in efficiency (Waman et al., 2022), and DS may be more active due to the presence of larger raindrops, potential adaptations for a scale‐adaptive RaFSIP scheme (Chen et al., 2023) could be more urgent than in stratiform clouds. This is because of the scale dependence of LWC, which can be an important input for predicting the effect of HM.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of machine learning (ML, i.e., data-driven models) capabilities has fostered new approaches to improving parameterizations (Gentine et al, 2018). Examples include replacing computationally intensive physical parameterizations with ML emulation (Keller & Evans, 2019;Krasnopolsky et al, 2005Krasnopolsky et al, , 2010Lagerquist et al, 2021;O'Gorman & Dwyer, 2018;Perkins et al, 2023) and training ML against observations (Chen et al, 2023;McGibbon & Bretherton, 2019;Watt-Meyer et al, 2021) or more accurate and computationally intensive parameterizations (Chantry et al, 2021). ML parameterizations for coarse-grid models have been trained on coarsened (coarse-grained) outputs of fine-grid or super-parameterized reference simulations, for example, to predict the effect of the full physics parameterization (Brenowitz & Bretherton, 2019;Han et al, 2020;Rasp et al, 2018;Watt-Meyer et al, 2024;Yuval et al, 2021), or a column-wise correction to the coarse-grid model physics (Bretherton et al, 2022;Clark et al, 2022;Kwa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This motivated us to use ML to also improve the simulated cloud distributions. Grundner et al (2022Grundner et al ( , 2023 and Chen et al (2023) have developed ML parameterizations of fractional cloud cover trained on coarsened fine-grid output and observations, and they showed that these parameterizations can improve upon the skill of existing physically based parameterizations. We extend such work here by demonstrating that ML-predicted cloud statistics, including fractional cloud cover and ice and liquid cloud condensate mixing ratios, can improve the offline simulation of coarse model radiative fluxes, given careful attention to the vertical overlap of fractional cloud cover within grid columns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al (2021) proposed a ML trigger function for a deep convection parameterization by learning from field observations, demonstrating its superior accuracy compared to traditional CAPE-based trigger functions. Chen et al (2023) developed a neural network-based cloud fraction parameterization, better predicting both spatial distribution and vertical structure of cloud fraction when compared to the traditional Xu-Randall scheme (Xu & Randall, 1996). Krasnopolsky et al (2013) prototyped a system using a neural network to learn the convective temperature and moisture tendencies from cloud-resolving model (CRM) simulations.…”
Section: Introductionmentioning
confidence: 99%